ASIMILASI BUDAYA TIONGHOA DAN BUDAYA JAWA DI SURAKARTA PADA TAHUN 1966-1998 DAN RELEVANSI BAGI PENDIDIKAN MULTIKULTURAL - Fitrianto, Romadoni Huda (Candi, 2015)
The aim of this research are to find out: (1) the background of Chinese and Javanese cultural assimilation in Surakarta 1966-1998, (2) The process of Chinese and Javanese cultural assimilation in Surakarta 1966-1998, (3) The impact of Chinese and Javanese cultural assimilation after 1966-1998, (4) The relevance of the research result of Chinese-Surakarta ethnic assimilation in 1966-1998 for multicultural education.The method used in this research are qualitative research methods. The steps taken in this method including data collection, data reduction, data analysis, presentation of data, and conclusion.The result of this research are : (1) The background of Chinese and Javanese cultural assimilation are caused by internal factor and external factor. Internal factor include the condition of Chinese community in the middle of the Javanese majority and economic problem. The external factor are appeared because of the New Order government policy. (2) The process of Chinese and Javanese cultural assimilation are divided into two periods, Old Order period led by Soekarno and New Order period led by Soeharto. (3) The impact of Chinese and Javanese cultural assimilation are contained in performing art and celebration day that contains cultural combination between Chinese and Javanese culture. (4) The result of this research are relevant with education field. Particularly as additional teaching materials for multicultural education in high school education.